Miocene divergence for Texoreddellia? An important component of the cave-adapted fauna of Texas and northern Mexico - Espinasa, Luis; Sprouse, Peter; Posso, Kara; Mitchell, Andrew; Espinasa, Monika; Lin, Jonathan (Zootaxa, 2023)
The genus Texoreddellia (Zygentoma; Nicoletiidae) is an important component of the cave-adapted fauna of Texas and northern Mexico. Specimens are often found in caves in central Texas. They are less common in western Texas and Coahuila, Mexico. We describe a new species, Texoreddellia chihuahuensis n. sp., from Chihuahua, Mexico, greatly expanding the range for the genus. The new species is found in an isolated karstic zone, far removed from the other cave forming areas inhabited by Texoreddellia spp. Phyletic analyses show the species to be the most basal and earliest to diverge within the genus. When compared to a calibrated molecular clock of the 16S rRNA for nicoleiids, its sequence supports a divergence of roughly 20 mya. Such a date is congruent with the geological origins of the Rio Grande and the Pecos River. Structural deformations coupled with long term erosion and downcutting through major river basins may have contributed in forming biological barriers that influenced speciation and isolation, especially between the western and eastern species of Texoreddellia.